A genetic variant in the TRAF1/C5 gene lead susceptibility to active pulmonary tuberculosis by decreased TNF-α levels. (October 2021) - Souza de Lima, Dhêmerson; Fadoul de Brito, Carolina; Cavalcante Barbosa, Aguyda Rayany; Brasil de Andrade Figueira, Mariana; Maciel Bonet, Julio César; Walzer, Joseph; Ramasawmy, Rajendranath; Ogusku, Mauricio Morishi; Sadahiro, Aya; Boechat, Antonio Luiz
Abstract: Host genetics are important to consider in the role of resistance or susceptibility for developing active pulmonary tuberculosis (TB). Several association studies have reported the role of variants in STAT4 and TRAF1/C5 as risk factors to autoimmune diseases. Nevertheless, more data is needed to elucidate the role of these gene variants in infectious disease. Our data reports for the first time, variant rs10818488 in the TRAF1/C5 gene (found 47% of the population worldwide), is associated with susceptibility (OR = 1.51) to development TB. Multivariate analysis evidenced association between rs10818488 TRAF1/C5 and risk to multibacillary TB (OR = 4.18), confers increased bacteria load in the lung, indicates a decreased ability to control pathogen levels in the lung, and spread of the pathogen to new hosts. We showed that the "loss-of-function" variant in TRAF1/C5 led to susceptibility for TB by decreased production of TNF-α. Our results suggest the role of variant TRAF1/C5 in susceptibility to TB as well as in clinical presentation of multibacillary TB. Graphical abstract: Image 1 Highlights: - TRAF1/C5 genetics seems to contribute to susceptibility for active pulmonary TB development. - TRAF1/C5 rs10818488 is associated with clinical multibacillary TB. - Mtb H37Rv was the most common specie in the Brazilian Amazon. - The individuals heterozygous for the TRAF/C5 rs10818488 showed decreased TNF-α levels.